Al Furuq al Islamiyyah - Syarif Zubaedah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
The emergence of religious sects has caused fidgetiness among society, ether in religious community itself or in social interaction in general. Historically, the emergence of religious sects takes place through times and centuries. It emerged by the time the religion was born. In Islamic history for instance, it has been widely known that there are genesis of the sects of khawarij and syiah in the phase of shahabah (companion of the Prophet Muhammad). Recently, in Indonesia especially, some sects considered as deviated, such as Jamaah Ahmadiyah, Al Qiyadah Al Islamiyyah, and Quran Suci have emerged. This has caused strained situation among society. In many regions, people massively protested against the existence of the sects. Often, it was followed by damaging the properties of the sects, such as houses and mosques. This article describes definition and characteristics of religious sects, whether it is good or deviate. This article also elucidate the causal factors of the emergence of those sects as well as its impacts toward society’s life. The study shows that the right sects are those who persistently hold the norms and values of Al-Qur’an, Sunnah, and follow the behavior of the Companion. While the causal factors of the religious sects emergence include economic factor, political factor, and the divergence of way of thinking. The impact of the emergence of those various religious sects are aqidah divergence, political movement divergences, and adhering strictly to the sect and ignoring strictly to the others. This is such as Mu’tazilah differs fundamentally from Ahlussunnah wal jamaah, Khawarij differs from Syiah, Qadariyah differs from Jabariyah. Each sect claimed that its opinion is the truest and others’ is wrong or astray.Keywords: religious streams, causal factors, chracteristics, and social impact.